The penultimate peril - Snicket, Lemony; Helquist, Brett (New York : HarperCollins, 2005)
In this next-to-last chronicle of the lives of the Baudelaire orphans, the siblings pose as concierges at the Hotel Denouement to learn the identities and intentions of certain enemies, encounter characters from their past adventures, and ponder the nature of nobility and villainy.
Keywords: Orphans -- Juvenile fiction; Siblings -- Juvenile fiction; Hotels, motels, etc. -- Juvenile fiction